Executive functions in mid-life adults with mild sensorineural hearing loss compared with age-matched controls with normal hearing - Chandrashekar, Pooja; Nagaraj, Hema (The Egyptian journal of otolaryngology, 2024)
Purpose This study explores the relationship between sensorineural hearing loss (SNHL) in mid-life adults and cognitive function, focusing on executive functions. Given the projected rise in dementia cases, identifying modifiable risk factors for cognitive decline is imperative. SNHL has emerged as a potential risk factor, with hearing loss accounting for a substantial portion of dementia cases. However, the cognitive implications of SNHL in mid-life adults are not well understood. Method The study examined 50 participants, 25 with bilateral unaided mild SNHL (AHL) and 25 with normal hearing (ANH). A battery of audiological assessments and cognitive tests, including the Trail Making Test (TMT), was administered. TMT measures included direct scores (completion time and errors) and derived scores (difference, ratio, proportion, sum, and multiplication scores). Results The AHL group displayed significantly poorer peripheral hearing compared to the ANH group, as reflected in pure-tone audiometry, speech reception thresholds, and speech identification scores. Significant differences were observed in all direct and derived TMT measures except for the ratio and proportion scores. This suggests that while overall cognitive disturbances were evident in the AHL group, they were not exclusive to executive function deficits. Notably, we did not identify any statistically significant effects of hypertension, diabetes, smoking, alcohol consumption, or physical activity on TMT scores. Conclusion This study highlights the potential impact of SNHL on cognitive function in mid-life adults. Mid-life SNHL is associated with cognitive differences, emphasizing its role as a modifiable risk factor for future cognitive decline. This research underlines the need for further investigation into the cognitive effects of aided hearing and a multidisciplinary approach to understanding these alterations in cognitive function.